Latin, Old English and documentary practice at Worcester from Wærferth to Oswald. (26th April 2019) - Gallagher, Robert; Tinti, Francesca
Abstract: This article analyses the uses of Latin and Old English in the charters of Worcester cathedral, which represents one of the largest and most linguistically interesting of the surviving Anglo-Saxon archives. Specifically focused on the period encompassing the episcopates of Wærferth and Oswald ( c. 870 to 992), this survey examines a time of intense administrative activity at Worcester, contemporaneous with significant transformations in the political and cultural life of Anglo-Saxon England more generally. In doing so, this article argues that when writing in either Latin or the vernacular, charter draftsmen responded to a number of variables; language choice did not simply reflect varying levels of literacy. Furthermore, the frequent cases of code-switching found in tenth-century Worcester documents mark this community out as exceptional, suggesting that attitudes towards the interaction between the two languages could vary considerably between institutions.